Concentration of exports and patterns of trade: a time-series evidence of Malaysia - Hamid, Zarinah (Tennessee State University, 2010)
This paper investigates the magnitude of geographic as well as commodity concentration for Malaysia from 1970 to 2003 and how the pattern of trade and instability has changed over time. The instability index is regressed upon a set of explanatory variables including commodity concentration, geographic concentration and share of primary commodity exports. The results indicate that the commodity concentration appears as a significant variable in explaining the export earnings instability. The paper recommends Malaysia takes several measures in order to remain immune from negative effects of instability. They include the continuous effort to stay competitive by maintaining productivity higher than production cost, to diversify as well as broaden its industrial base and constantly find new markets for new products.These measures, in the presence of right macro-economic policies supplemented by increasing foreign direct investment with intra-regional trade paved the way for market-friendly approach backed by a number of liberalization measures.